(Ross-border organized crime,(international cooperation, methods of control - Sha‘anbi, Fouad (Journal of Economic, Administrative and Legal Sciences, 2018)
The organized crime who infiltrates through the border between states for various account , its risks have increased for the human societies. For this, we must deal with this evil in a way effective and realistic. This can be achieved only by the eradication of its causes and roots of the middle social and economic especially in the regions where sevient poverty and misery.The therapy of this scourge is not limited to adoption of dissuasive measures on the national and international level, but also includes the application of preventive measures such as social justice and prosperity for the individual or that it is. One can also say that these recent actions could be more effective in the policy to combat organized crime.
Keywords: organized crime; globalization and cosmopolitanism; international cooperation